Kinetic study of Mongolian coals by thermal analysis - S, Jargalmaa; G, Tsatsral; M, Battsetseg; D, Batkhishig; A, Ankhtuya; J, Namkhainorov; B, Bat-Ulzii; B, Purevsuren; B, Avid (Mongolian Journal of Chemistry, 2018)
Thermal analysis was used for the thermal characterization of the coal samples. The experiments were performed to study the pyrolysis and gasification kinetics of typical Mongolian brown coals. Low rank coals from Shivee ovoo, Ulaan ovoo, Aduun chuluun and Baganuur deposits have been investigated. Coal samples were heated in the thermogravimetric apparatus under argon at a temperature ranges of 25-1020ºC with heating rates of 10, 20, 30 and 40ºC/min. Thermogravimetry (TG) and derivative thermogravimetry (DTG) were performed to measure weight changes and rates of weight losses used for calculating the kinetic parameters. The activation energy (Ea) was calculated from the experimental results by using an Arrhenius type kinetic model.